A novel sodium alginate/cellulose nanofiber self-supported hydrogel membrane and its filtration performance. (December 2022) - Cai, Rong; Zhou, Yueyun; Hu, Jiawei; Lu, Jiawei; Fan, Xiaokun; Chen, Ying; Ding, Meng; Rong, Jingjing; Liu, Wenyong; Chen, Yi
Abstract: A polysaccharides sodium alginate (SA)/cellulose nanofiber (CNF) composite hydrogel (S-Cx) was prepared for applying as a self-supported filtration membrane to solve the problem of membrane fouling. By using "cooking" method to deal with the SA solution and adding CNF in the synthesis process, the hydrogel membrane shows excellent mechanical properties. Through the pore-making and large pressure applying, the flux of S-Cx membrane could reach 71.5 Lm −2 h −1, which is similar to some hydrophobic membranes. The excellent fouling resistance and long-term application ability were also found in the filtration. Moreover, its rich ionic groups such as carboxyl and hydroxyl groups endow the membrane with a strong ability to intercept the heavy metal ions and ionic dyes based on the differential mechanisms. All of the characteristics make it a potential filter membrane.